Religion, moral attitudes and economic behavior [dataset] - Kirchmaier, Isadora; Prüfer, Jens; Trautmann, Stefan T. (Universität, 2018)
Using data for a representative sample of the Dutch population with information about participants’ religious background, we study the association between religion and moral behavior and attitudes. We find that religious people are less accepting of unethical economic behavior (e.g., tax evasion, bribery) and report more volunteering. They are equally likely as non-religious people to betray trust in an experimental game, where social behavior is unobservable and not directed to a self-selected group of recipients. Religious people also report lower preference for redistribution. Considering differences between denominations, Catholics betray less than non-religious people, while Protestants betray more than Catholics and are indistinguishable from the non-religious. We also explore the intergenerational transmission and the potential causality of these associations.